Analysis of parental burnout conditions during the Covid-19 pandemic in Indonesia - Bella Yugi Fazny (Journal of Advanced Guidance and Counseling, 2021)
Purpose -  This research aimed to describe the level of parental burnout of parents in children during the COVID-19 pandemic.  Method - Measurements were carried out using the Maslach Burnout Inventory (MBI) instrument. Participants in this research amounted to 164 people spread across various regions in Indonesia.Result - 15% of parents experienced a high level of parental burnout, 64% of parents experienced a moderate level of parental burnout and 21% of parents experienced a low level of parental burnout in the care of children under 18 years old during the COVID-19 pandemic. The results of another survey of the need for assistance were that 96% of parents answered that it was necessary to provide a self-healing guidebook related to mental health issues (self-therapy).Implications – This research has an impact on developing a first aid handbook to assist parents in identifying and dealing with parental burnout independently through self-healing therapy.Originality – This research is an overview of the need for assistance that can be provided or developed by further researchers especially in the care of children under 18 years old during the COVID-19 pandemic.***Tujuan - Penelitian ini bertujuan untuk mendeskripsikan tingkat parental burnout orang tua pada anak selama masa pandemi COVID-19.Metode - Pengukuran dilakukan dengan menggunakan instrumen Maslach Burnout Inventory (MBI). Partisipan dalam penelitian ini berjumlah 164 orang yang tersebar di berbagai daerah di Indonesia.Hasil - 15% orang tua mengalami tingkat kelelahan orang tua yang tinggi, 64% orang tua mengalami tingkat kelelahan orang tua yang sedang dan 21% orang tua mengalami tingkat kelelahan orang tua yang rendah dalam mengasuh anak di bawah usia 18 tahun selama masa pandemi COVID-19. Hasil survei lain tentang perlunya pendampingan adalah 96% orang tua menjawab perlu menyediakan buku panduan self-healing terkait masalah kesehatan mental (self-therapy).Implikasi - Penelitian ini berdampak pada mengetahui praktisi kesehatan mental dan psikiatri dapat mengembangkan buku pegangan pertolongan pertama untuk membantu orang tua dalam mengidentifikasi dan menangani kelelahan orang tua secara mandiri melalui terapi penyembuhan diri.Originalitas - Penelitian ini merupakan gambaran tentang perlunya bantuan yang dapat diberikan dan atau dikembangkan oleh peneliti selanjutnya khususnya dalam pengasuhan anak di bawah 18 tahun selama masa pandemi COVID-19.